Quantitative Evaluation of Shale Pore Structure Using Nuclear Magnetic Resonance Data - Kun MENG (Chinese Journal of Magnetic Resonance, 2021)
The pore structure of shale gas reservoir is complex and heterogeneous, leading to great challenges in reservoir characterization and effectiveness evaluation. In order to establish a quantitative evaluation method for pore structure of the shale gas reservoir, 20 cores of the second member of Doushantuo Formation in Yichang area, western Hubei were selected as the experimental sample. An echo interval of 0.069 ms was used to carry out nuclear magnetic resonance (NMR) experiments under 100% salt water saturation. The obtained T2 spectra were analyzed with the multifractal characteristics method, and the parameters sensitive to the pore structure of the shale reservoirs were extracted. A method and a standard to classify shale reservoir types were developed, based on the minimum and maximum generalized fractal dimension difference (Dmin-Dmax) and spectral width (Δα). This method is of great significance for improving the prediction accuracy of shale gas reservoirs and guiding development and selection.